Innovation of Differentiated Flipsains Integrated with STEAM and Tri-N in Increasing Creativity of Elementary School Students - Endah Krisnajati; Ana Fitrotun Nisa; Heri Maria Zulfiati (Jurnal Ilmiah Sekolah Dasar, 2024)
Creativity is one of the skills that a person must have in order to survive in this era of uncertainty. Creativity needs to be developed from an early age, including in elementary school learning. This research aims to develop science flipbook media (flipsains) based on differentiated learning integrated with STEAM and Tri-N approaches in increasing elementary school students' creativity. This research uses a development research method with ADDIE stages: analysis, design, development, implementation, and evaluation. The subjects studied in this research were fourth grade elementary school students, totalling 17 students in the limited trial and 56 students in extensive trial. Data collection techniques in this research were carried out using observation, interviews and questionnaires. The analysis technique for this research was carried out using qualitative and quantitative descriptive methods. The results of this research show that flipsains media was produced with characteristics based on differentiated learning which was designed with an initial assessment, equipped with various kinds of videos and various projects. Flipsains was also developed according to elements of the STEAM approach and the Tri-N Method. The validation results show that the flipsains developed is said to be valid with validation results of 90.2% with very feasible criteria. The developed flipsains has also proven to be effective in increasing elementary school students' creativity as evidenced by the increase in observation scores of students' creativity skills in limited trials and extensive trials.